Measuring the Level of Customer Satisfaction at Soekarno Hatta Airport Departure Terminal 3 on the Availability of Customer Favorite Brands - Boy Fajar Prasetiyo; Mohammad Alif Widodo; Juliater Simarmata (Dinasti Publisher, 2024)
Articles related to measuring the level of customer satisfaction at Soekarno Hatta Airport Departure Terminal 3 on the availability of customer favorite brands are in the domain of marketing management science. The aim of this research is to formulate a hypothesis regarding the interrelationship of various aspects, which will then be used as a basis for further research in the field of human resource management. This research uses a qualitative descriptive research methodology. The data used in this research comes from previous research which is still relevant to this research. Information is collected from leading scientific online platforms, such as Publish or Perish, Google Scholar, digital reference books, and the journal Sprott. The results obtained from this research are presented as follows: 1) Brand availability plays a role in measuring the level of customer satisfaction at Soekarno Hatta departure terminal 3; 2) Terminal infrastructure plays a role in measuring the level of customer satisfaction at Soekarno Hatta departure terminal 3; and 3) Product service plays a role in measuring the level of customer satisfaction at Soekarno Hatta Departure Terminal 3.